(untitled) (Canadian Perspectives on Academic Integrity, 2020)
This editorial shared the contemplations of three symposium participants who are also scholars and educators in the field of academic integrity: Jennie Miron, PhD, Brenda M. Stoesz, PhD, and Brandy Usick, MEd. We share our individual reflections that underscores our optimism and enthusiasm for the future of the field of academic integrity scholarship within Canada.